Teori ‘Asabiyyah Ibn Khaldun dalam Perspektif Hukum Islam (Theory of 'Asabiyyah Ibn Khaldun in Islamic Law Perspective) - Mulia, Muji (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2019)
The theory of 'Asabiyyah (Solidarity of groups, fanaticism of tribes or nepotism) is the fruit of the Ibn Khaldun think. The birth of the theory of 'Asabiyyah is not separated from his observation of the condition of Muslims when it is in the interfaith and seize power by relying on the solidarity of Groups, group. This article is about to examine the theory of 'asabiyyah Ibn khaldun. This article is reviewed with a historical and normative approach. The results showed that in order to practice this 'Asabiyyah theory does not lead to evil and negative, according to Ibn Khaldun's opinion, it is the only solution to control and control the operation of the group. Religion is instrumental in lowering the tension of this asabiyyah practice. Although Ibn Khaldun has explained 'Asabiyyah (Solidarity Group, fanaticism group) part of Sunnatullah that cannot be eliminated from human life, we should also see from the Islamic eyewear in this case Islamic law on the practice of ' Asabiyyah (Solidarity Group). In the view of Islamic law, the practice of 'Asabiyyah (solidarity Group) is not allowed to be banned by reason of violating the purpose of establishing Islamic law itself. The purpose of established Islamic law is to create the benefit of mankind. While the practice of solidarity group, Fanatime tribe, and nepotism gave misery, the distress, hostility and destruction of the joints of human life, both in the world and in the hereafter.